Efficacy of Miswak as an Adjunct to Tooth Brushing for Gingival Health: A Clinical Study in Qassim - Alsaegh, Mohammed Khalid; Awinashe, Vaibhav; Alghofaili, Meshal Mohammed; Alshyai, Hammad Saleh; Altorisy, Abdullah Bader; Almazyad, Rayan Khaled (Nigerian Journal of Basic and Clinical Sciences, 2025)
Context:There is a global rise in the prevalence of oral diseases, increasing the need for oral hygiene methods that are safe, effective, economical, and easily accessible. Plant-derived chewing sticks have long been used as traditional oral hygiene tools. Salvadora persica, commonly known as Miswak, is the most widely used plant for this purpose.Aim:To evaluate the efficacy of Miswak as an adjunct to tooth brushing in improving gingival health among male patients in Qassim.Materials and Methodology:This case–control clinical study was conducted at Qassim University Medical City Dental Hospital, Al-Rass, involving 30 male patients. Participants used tooth brushing alone for 14 days, followed by 14 days of tooth brushing combined with Miswak use. Plaque Index (PI) and Gingival Index (GI) scores were recorded at baseline (T0) and after each intervention period.Results:There was a statistically significant reduction in Plaque Index between baseline and the tooth brushing plus Miswak period (p = 0.01214). A similar significant improvement was observed in Gingival Index scores (p = 0.011062813). Post-hoc t-test analysis showed a statistically significant difference in Plaque Index scores between T0 and the TB+M 14-day period (two-tailed p = 0.004525). Gingival Index scores also showed a statistically significant improvement between T0 and TB+M 14 days (two-tailed p = 0.00553982).Conclusion:Within the limitations of this study, the combination of tooth brushing and Miswak significantly improves plaque control and gingival health.
Keywords: Adjunct; Miswak; Gingival health; Tooth brushing